POLIMORFISME GEN MITOKONDRIA 16S IKAN BAUNG (Hemibagrus nemurus Valenciennes, 1840) DARI SUNGAI PROGO, MAGELANG, JAWA-TENGAH - Tuty Arisuryanti; Ulfa Dianiputri; Katon Waskita Aji (Berkala Ilmiah Biologi, 2022)
Abstract: Asian redtail catfish (Hemibagrus nemurus Valenciennes, 1840) is one of Indonesian native fish species with high economic potency. However research on genetic variation of Asian redtail catfish in Indonesia is very limited. Therefore, this study purposed to identify and analyze the mitochondrial gene polymorphism 16S of Baung fish (H. nemurus) from the Progo River, Magelang, Central Java. The method used in this study was the PCR method with universal primers 16Sar and 16Sbr. Intraspecific genetic variation was conducted by combining mitochondrial gene 16S sequence data of five Asian redtail fish (H. nemurus) samples from Progo River (BGM 02-06) and five Asian redtail fish samples from GenBank. BLAST, DnaSP, DNASTAR, GeneStudio,, MEGA, Mesquite, and NETWORK programs were used to analyze the data obtained. The results showed there were no genetic differences among the Asian redtail fish from Progo River indicating no intrapopulation genetic variation of the fish species. Conversely, the intraspecific genetic divergence was between 0.20% and 2.21% with an average of 0.92%. Analysis of intraspecific genetic variations detected 5 different haplotypes and 15 variable sites with 5 parsimony informative sites. Haplotype diversity and nucleotide diversity values were 0.756 ± 0.130 and 0.00812 ± 0.00294 respectively. Analysis of phylogenetic and haplotype network revealed BGM 02-06 formed a specific haplotype that was separated from other haplotypes. Molecular markers for Asian redtail fish (H.nemurus) from the Progo River, Magelang, Central Java based on the 16S mitochondrial gene can use this specific haplotype.